Liquid-Phase Homogeneous Catalytic Oxidation of Gas Oil: Elucidation of Complex Chemical Transformation Network - Syed Mumtaz Danish Naqvi; Muhammad Ashraf Kamal; Syed Mohib Raza Kazmi; Kashif Riaz; Fasihullah Khan (Journal of Basic & Applied Sciences, 2015)
An attempt has been made to elucidate the extremely complex chemical changes that take place when gas oils (middle distillates such as high speed diesel) are subjected to liquid phase homogeneous oxidative processing in the presence of the redox couple Co(III)/Co(II). For this purpose dilute solutions of gas oil in wet acetic acid have been treated with air under carefully controlled conditions of temperature, pressure and air flow rate. Reaction products are extracted in chloroform from an ice cold aqueous solution of the reaction mixture. Both instrumental (FTIR) and kinetic analyses endorse each other and thereby prove the sequential nature of the reaction resulting in the formation of diverse products through decomposition of the intermediate hydroperoxides, which are unstable in the presence of the catalytic redox couple Co(III)/Co(II).